Assessment of sugar cane straw ash (SCSA) as pozzolanic material in blended Portland cement: Microstructural characterization of pastes and mechanical strength of mortars - Moraes, J. C.B. [UNESP] (2015)
Abstract The aim of this paper is to assess the pozzolanic reactivity of sugar cane straw ash (SCSA) obtained through an auto-combustion process and the mechanical properties of SCSA-containing systems. Characterization of SCSA (X-ray diffraction, chemical composition, particle size, and microscopy) and reactivity studies on hydrated lime/SCSA and Portland cement/SCSA pastes through infrared spectroscopy, thermogravimetric analysis, and microscopy demonstrated the high pozzolanic activity. This reactivity made it possible to achieve good mechanical properties in mortars in which 15-30% of the cement was replaced by SCSA. After 90 days of curing, the SCSA fixed 100% of the lime present in lime/SCSA pastes, and the compressive strength of mortars containing SCSA reached 44 MPa, a value similar to those found for control mortars after the same number of curing days. The results for the microstructural and mechanical properties showed that SCSA is a good pozzolanic material.